Clinical features of primary intestinal follicular lymphoma: A single-center retrospective study - Chun-Lin Ying; Tian-Qi Zhao; Qin-Xue Pu; Han-Cheng Huang; Wei Liu (Journal of International Medical Research, 2026)
Objective To characterize the clinical features of primary intestinal follicular lymphoma and provide insights into its diagnosis and management. Methods We retrospectively analyzed the clinical, endoscopic, imaging, pathological, and long-term follow-up data of eight patients with primary intestinal follicular lymphoma who were admitted between January 2019 and August 2025. Results The mean patient age was 58.13 years, and 75.00% of patients were women. Abdominal pain (62.50%) was the most common clinical manifestation, and 62.50% of patients presented with severe complications, including gastrointestinal bleeding or obstruction. Lesions were distributed across multiple intestinal segments. The most characteristic endoscopic finding was lymphoid follicle-like elevation (50.00%), which could be mistaken for a polyp. Histopathological examination showed that 62.50% of lesions were confined to the mucosa or submucosa. All specimens were positive for cluster of differentiation 20, B-cell lymphoma 2, and B-cell lymphoma 6. Asymptomatic patients were managed with a watch-and-wait strategy and had favorable outcomes, whereas patients requiring surgery because of severe complications associated with deeper infiltration had poorer outcomes. Conclusion Primary intestinal follicular lymphoma is a rare, predominantly indolent B-cell lymphoma whose diagnosis relies on histopathological and immunohistochemical evaluation. Although outcomes in this small series were generally favorable, patients with severe complications may have poorer outcomes. Larger multicenter prospective studies incorporating genetic profiling are needed to validate these observations and further inform individualized management strategies.